2022
DOI: 10.3389/fped.2022.857034
|View full text |Cite
|
Sign up to set email alerts
|

The First United Arab Emirates National Representative Birth Cohort Study: Study Protocol

Abstract: BackgroundIn recent years, the prevalence of non-communicable diseases (NCDs) has escalated. Evidence suggests that there are strong associations between nutrition in early life and the risk of disease in adulthood. This manuscript describes the study protocol of the First United Arab Emirates National Representative Birth Cohort Study (UAE-BCS), with the objective of investigating nutrition and lifestyle factors in the first 1,000 days of life. The main aims of the study are (1) to address critical issues rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The population distribution of employees in this study was similar in terms of the country distribution of expatriates and their ethnicities [21,22]. The country's population is largely constituted of males who come to work in industries and construction sectors, very similar to other Gulf cooperation countries [4].…”
Section: Key Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The population distribution of employees in this study was similar in terms of the country distribution of expatriates and their ethnicities [21,22]. The country's population is largely constituted of males who come to work in industries and construction sectors, very similar to other Gulf cooperation countries [4].…”
Section: Key Resultsmentioning
confidence: 52%
“…Moreover, the UAE is host to a larger number of expatriates, making up 88% of the entire population [3]. These three key characteristics highlighted here demonstrate the challenges when conducting a country versus employee population analysis and comparison [7,16,21]. The present study took those country characteristics into consideration and attempted to include as diverse pool of employees as possible.…”
Section: Key Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has previously reported to be between 7.7% among childbearing age women [41] to 21.6%, which was reported to be the second highest rate in the region, according to the latest ndings of meta-analysis [42]. Whereas, the prevalence of undiagnosed diabetes in the UAE population was reported to 14.6% [31,43].…”
Section: Key Resultsmentioning
confidence: 90%
“…In terms of chronic diseases in the UAE, this study found a low prevalence of chronic diseases compared with previous studies, this can be explained by the average age of the Employees. Chronic diseases account for more than 65% of deaths in the country [31] and the public health priority areas in the last 10 years have been cardiovascular diseases, road injuries, cancers and respiratory disorders [32].…”
Section: Key Resultsmentioning
confidence: 99%